Identity Politics and Democratic Deliberation in Indonesian Muslim Society - Ujang Komarudin (Postgraduate, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2026)
Identity politics has become an increasingly prominent feature of democratic contestation in Indonesia, particularly within its Muslim-majority society. Although previous studies have primarily treated identity politics as an electoral strategy or a source of polarization, its consequences for the communicative quality of democracy remain insufficiently examined. This study analyzes the transformation of identity politics across the 2017 Jakarta gubernatorial election, the 2019 presidential election, and the 2024 general election through Jürgen Habermas's theory of communicative rationality. Employing a qualitative multiple-case study, the research uses Norman Fairclough's Critical Discourse Analysis to examine textual framing, discursive circulation, and the wider social practices through which identity narratives were produced and legitimized. Habermas's validity claims and distinction between communicative and strategic action are then used as normative criteria for evaluating deliberative quality. The findings show a movement from explicit religious mobilization in 2017, to antagonistic partisan polarization in 2019, and to affective, personalized, and algorithmically mediated identity branding in 2024. Across the three cases, identity discourse increasingly privileged symbolic resonance, emotional mobilization, and electoral effectiveness over reciprocal reason-giving. Nevertheless, religious identity is not inherently inimical to deliberative democracy. When articulated through shura, tabayyun, justice, and publicly accessible reasoning, Islamic values can enrich rather than narrow the public sphere. The article contributes a longitudinal, discourse-centered account of identity politics and proposes an Islamic-Habermasian framework for reconstructing democratic deliberation in Muslim-majority societies.